Coeliac disease: factors affecting the transition and a practical tool for the transition to adult healthcare. Issue 9 (1st November 2018) - Zingone, Fabiana; Massa, Serana; Malamisura, Basilio; Pisano, Pasquale; Ciacci, Carolina
Abstract : Background: As of now, no established model for the transition from childhood to adulthood in coeliac disease exists. We aim to describe the dietary compliance and the quality of life of a population of young coeliac disease patients around transition age and to develop a practical tool (TRANSIT‐CeD disk) which can be used during the transition process effectively to transmit young adults to the adult healthcare giver. Methods: We consecutively recruited all coeliac disease patients with a paediatric diagnosis (≤16 years) and aged between 9 and 20 years at the time of the study. The patients were asked to answer some questions concerning their adherence to a gluten‐free diet, knowledge about coeliac disease, relationship with healthcare givers and quality of life. Results: We included 58 subjects, mean age 14.5 ± 3.6 years, of which 62% were girls/young women. We observed that dietary compliance was independently and positively related to age at diagnosis and coeliac disease knowledge, while quality of life was only independently and positively related to coeliac disease knowledge. Conclusion: A good coeliac disease knowledge is positively related to dietary compliance and quality of life. With the help of the TRANSIT‐CeD disk we proposed, paediatricians and adult gastroenterologists can follow the patients during the transition and identify some points to work on.